2014
DOI: 10.1175/jas-d-13-0125.1
|View full text |Cite
|
Sign up to set email alerts
|

The Transition to a Subtropical Jet Regime and Its Maintenance

Abstract: An abrupt transition from a merged jet regime to a subtropical jet regime is analyzed using a two-layer modified quasigeostrophic (QG) spherical model. Unlike the common version of QG models, this model includes advection of the zonal mean momentum by the ageostrophic mean meridional circulation, allowing for a relatively realistic momentum balance in the tropics and subtropics. The merged jet is a single jet inside the Ferrel cell created by a merging of the subtropical and eddy-driven jets, and the subtropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 36 publications
5
36
0
Order By: Relevance
“…Under QBOe, the QBO-induced meridional circulation appears to cause a poleward shift of the subtropical jet, which consequently encourages upward wave propagation at midlatitudes because of the increased baroclinicity (Lachmy and Harnik 2014). A similar shift of the jet was also found by Garfinkel and Hartmann (2011), though the effect they identified is only significant in early and late winter.…”
Section: Conclusion and Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Under QBOe, the QBO-induced meridional circulation appears to cause a poleward shift of the subtropical jet, which consequently encourages upward wave propagation at midlatitudes because of the increased baroclinicity (Lachmy and Harnik 2014). A similar shift of the jet was also found by Garfinkel and Hartmann (2011), though the effect they identified is only significant in early and late winter.…”
Section: Conclusion and Discussionmentioning
confidence: 62%
“…These newly generated planetary waves propagate upward, having a positive feedback with the arching zonal winds in the subtropics to midlatitudes and acting to drive an enhanced poleward meridional circulation in the lower stratosphere, thus contributing to the weaker and warmer polar vortex. The poleward shift of the subtropical jet also results in less baroclinic planetary wave activity at high latitudes, as a result of upward-propagating baroclinic waves favoring propagation toward regions of high baroclinicity (e.g., Lachmy and Harnik 2014). While our analysis does provide certain evidence for the HTE causality in terms of wave driving, we appreciate that our arguments are based on correlations drawn from reanalysis data.…”
Section: Conclusion and Discussionmentioning
confidence: 75%
“…However, the position of the jet relative to the meridional circulation differs greatly between the winter and summer seasons. The jet is located between the Hadley cell and the wave‐driven indirect Ferrel cell in winter, whereas it sits completely inside the Ferrel cell in summer [e.g., Lee and Kim , ; Lachmy and Harnik , ]. The location of the summer jet inside the wave‐driven circulation indicates that the jet must be strongly influenced by eddies.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, in Son and Lee (2005), the jet changed from an eddy-driven state to a merged eddy-thermally driven state when the tropical forcing was strengthened or the midlatitude baroclinicity weakened. Recently, Lachmy and Harnik (2014) showed that the important factor by which the midlatitude baroclinicity affects the jet stream type is the strength of the eddies. Moreover, a change in jet type can be induced by changing eddy damping while keeping the mean flow forcing fixed.…”
Section: Introductionmentioning
confidence: 99%
“…equatorward and is affected by both thermal and eddy driving (cf. Son andLee 2005: Lachmy andHarnik 2014). At the same time, the transition to a merged jet state will also weaken eddy amplitudes by trapping the upper-level disturbances equatorward of the latitude of strongest surface baroclinicity and making baroclinic growth less efficient (Nakamura and Sampe 2002).…”
mentioning
confidence: 99%